Study on National Standards of Education (SNP) Achievement at Samarinda State Agriculture Development School (SPP) - Maryati Maryati (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2019)
The purpose of this study is to describe strengths and weaknesses of SMK-SPP Samarinda towards the achievement of National Education Standards particularly management, facilities and infrastructure, financing standards and determine SMK-SPP Samarinda Strategy in compliance with national education standards, especially management standards, facilities and infrastructure, as well as financing. Results of the research demonstrated that the strengths of SMK SPP are as follows: sufficient field-study area; availability of main facilities and infrastructure; competitive study programs; ISO 9001-2008 certified; and A-accredited school. Meanwhile, the weaknesses of SMK SPP are: inadequate human resources, both in quantity and quality; education facilities and infrastructure are still not based on information and communication technology; financial dependent; inadequate workshop facilities for selling agricultural products. Strategies that need to be developed to achieve national education standard based on SWOT analysis in SMK SPP Samarinda are as follows: Institutional Strengthening, School of Management Improvement, Learning Quality Improvement, and School Relations with Stakeholders strengthening.